SHM_95327_HST_3D Femur-Shaped Grindstone - National Historical Museums (National Historical Museums, 2026)
Structured Light 3D model of a femur-shaped grindstone (Swedish: Lårbensformad slipsten) from the Swedish Middle Neolithic, collected in the field from Alm in Orebro and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=409

Link to Sök I Samlingarna

https://samlingar.shm.se/object/772C97CE-5B8B-4813-87AC-D001092A21F0
Keywords: Archaeology; Archaeology; Archaeology/history; Structured Light Scanning; 3D Model; Museum Object; Dynamic Collections; Alm; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi